ESTETIKA DAKWAH DALAM LAGU JAWA - Tamyizul Ibad (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2010)
The study elaborates the arts of dakwah in the Javanese songs; Sluku-sluku Bathok and Turi-turi Putih. Both songs are one of the dakwah strategies conducted by the previous Ulemas in order that the society could accept the dakwah effectively. The use of the Javanese songs in the dakwah has become a particular characteristic of acculturation of Islam and Javanese culture. In fact, Javanese society has pleasantly accepted the Islamic dakwah.